AN ANALYSIS OF GRAMMATICAL ERROR IN CONSTRUCTING SENTENCES IN SIMPLE PRESENT TENSE AND SIMPLE PAST TENSE MADE BY THE LEARNERS AT GAMA INTEGRA PEDAN KLATEN IN 2006 / 2007 ACADEMIC YEAR - RAFI’ATUN , SITI (2007)
The objectives of the study are giving identification and description of the kinds of grammatical errors, knowing the frequency of grammatical error and knowing the dominant error made by the learners of Gama Integra Pedan Klaten in constructing Simple Present Tense and Simple Past Tense in 2006/2007 academic year. The writer uses descriptive method. In this study the data are sentences and the source of data is learners’ answer. Test as ins trument to collect the data. The technique of analyzing the data in this research through analyzing the grammatically incorrect by giving mark to the wrong part, asking the learners to revise them, analysis the errors sentences, classifying the type of errors, counting each kind of errors in order to know the dominant of error, and interpreting the result of the study by giving some comments. This study shows that there are four kinds of grammatical errors in constructing simple present tense and simple pa st tense sentence made by the learners at Gama Integra Pedan Kl aten in 2006/2007 academic year. They are; addition error, misformation error, omission error, and mi sordering error. The frequency of addition error is 45, 25%, misformation error is 25, 2 6%, omission error is 24, 74%, and misordering error is 4, 74%. The dominant error is addition error.